Buddhist Psychology: A More Sustainable Alternative in Psychology - Ratanamethee, PhraSirirattanamethee; Takham, Panittha (Journal of Thammawat, 2024)
The purpose of this article was to apply the principles of Buddhism to solve problems by maintaining and developing the minds of people in society. It could be called the use of Buddhist psychology by bringing up Buddhist principles that emphasize the understanding of the natural reality of life, the causes of problems in life and methods for solving them. Understanding these would allow people in society to live peacefully, reducing or eliminating suffering and improving mental quality. Buddhist psychology was suitable to be applied to everyone who was open to accepting and takes time to train one's mind no matter what kind of life situation one was in.